Interaction of a novel antimicrobial peptide isolated from the venom of solitary bee Colletes daviesanus with phospholipid vesicles and Escherichia coli cells - Čujová, Sabína; Bednárová, Lucie; Slaninová, Jiřina; Straka, Jakub; Čeřovský, Václav (Journal of peptide science, 2014)
The peptide named codesane (COD), consisting of 18 amino acid residues and isolated from the venom of wild bee Colletes daviesanus (Hymenoptera : Colletidae), falls into the category of cationic α-helical amphipathic antimicrobial peptides. In our investigations, synthetic COD exhibited antimicrobial activity against Gram-positive and Gram-negative bacteria and Candida albicans but also noticeable hemolytic activity. COD and its analogs (collectively referred to as CODs) were studied for the mechanism of their action. The interaction of CODs with liposomes led to significant leakage of calcein entrapped in bacterial membrane-mimicking large unilamellar vesicles made preferentially from anionic phospholipids while no calcein leakage was observed from zwitterionic liposomes mimicking membranes of erythrocytes. The preference of CODs for anionic phospholipids was also established by the blue shift in the tryptophan emission spectra maxima when the interactions of tryptophan-containing COD analogs with liposomes were examined. Those results were in agreement with the antimicrobial and hemolytic activities of CODs. Moreover, we found that the studied peptides permeated both the outer and inner cytoplasmic membranes of Escherichia coli. This was determined by measuring changes in the fluorescence of probe N-phenyl-1-naphthylamine and detecting cytoplasmic β-galactosidase released during the interaction of peptides with E. coli cells. Transmission electron microscopy revealed that treatment of E. coli with one of the COD analogs caused leakage of bacterial content mainly from the septal areas of the cells.
Keywords: kationické antimikrobiální peptidy; electron microscopy; tryptofan; Protein Structure, Secondary; Hydrophobic and Hydrophilic Interactions; Hemolysis; Molecular Sequence Data; molekulární sekvence - údaje; Liposomes; Bee Venoms; permeabilita buněčné membrány; Escherichia coli; Tryptophan; antibakteriální látky; zvířata; sekundární struktura proteinů; včely; Fluorescence; Antimicrobial Cationic Peptides; Drug Design; Amino Acid Sequence; large unilamellar vesicles; Anti-Bacterial Agents; Bees; CD spectroscopy; Phospholipids; Cell Membrane Permeability; liposomy; racionální návrh léčiv; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; membrane permeabilization; fosfolipidy; fluorescence; Animals; wild-bee venom; antimicrobial peptides; hemolýza; hydrofobní a hydrofilní interakce; včelí jedy; sekvence aminokyselin